Examining the Effect of Export Restrictions on Medical Products under WTO during Covid-19 Pandemic - Anand Kumar Singh (Qubahan Academic Journal)
Export of medical instruments in midst of life-threatening pandemic crisis has increased significantly. However, the urgent supply of medical products faces the challenge of unprecedented protectionist restrictions introduced by several developed nations. These restrictions, introduced to avoid shortage of medical products in domestic market of such exporting countries, threaten the lives and livelihood of million others in immediate and urgent need of goods. The article examines the legality and effect of these restrictions under the extant WTO framework. Lastly, the article also highlights the necessity of international cooperation between nations to overcome partisan policies of self-interest and the imporatnce of collective efforts in this fight against a common threat.